Thyroid Cancer: Molecular Aspects and New Therapeutic Strategies. (12th July 2012) - Grande, Enrique; Díez, Juan José; Zafon, Carles; Capdevila, Jaume
Abstract : Despite that thyroid cancer accounts for over 90% of tumors that arise from the endocrine system, these tumors barely represent 2% of solid tumors in adults. Many entities are grouped under the general term of thyroid cancer, and they differ in histological features as well as molecular and clinical behavior. Thus, the prognosis for patients with thyroid cancer ranges from a survival rate of >97% at 5 years, in the case of differentiated thyroid tumors sensitive to radioactive iodine, to a 4-month median survival for anaplastic tumors. The high vascularity in these tumors and the important role that oncogenic mutations may have in the RAS/RAF/MEK pathway and oncogenicity (as suggested by activating mutations and rearrangements of the RET gene) have led to the development of multitarget inhibitors in different histological subgroups of patients. The correct molecular characterization of patients with thyroid cancer is thought to be a key aspect for the future clinical management of these patients.